The time horizon and Dasein-world relations in two Heidegger perspectives between 1927-1930 - Butierrez, Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
In the following work we will analyze the consideration of temporality in the Dasein-world relationship, based on two works by Heidegger. In particular, we will develop a historical-hermeneutical study of his elaborations around the time horizons, both in the SuZ period, and in his course in Freiburg from 1929-1930. In this framework we will seek to account for the differences in which such questions are articulated with respect to their relations with the ecstasies of Dasein. Together with this, we intend to argue that this difference and its displacement can be understood as a re-elaboration that articulates the relational understanding of Dasein already deployed in 1927.